Práticas sustentáveis na administração pública: a percepção de servidores técnico-administrativos da UFPB - Mourão, Querli Maria Bezerra (2023)
Higher Education Institutions (HEIs) are seen as environments that bring together multiple and interdisciplinary knowledge, which can be considered catalyser instruments in the process of institutionalization of the sustainability. In the Brazilian case, the Federal Institutions of Higher Education (IFES) need to incorporate policies aimed at sustainability as bodies of the Federal Public Administration (ADF), among which the Sustainable Management and Logistics Plan (PLS) stands out. It was observed that researches that addresses sustainability from the perspective of members from the academic community in IFES still represents a small share of the theme and thereby are concentrated on the perception of other actors, mostly using quantitative methodologies. In this sense, this research sought to understand the implementation of sustainable practices at the Federal University of Paraíba (UFPB) based on the perception of technical-administrative servants (TAEs) working at the Centre for Applied Social Sciences (CCSA), considering of the PLS. In particular, the objective was to contextualize the actions aimed at sustainability in the context of the campus I, to describe the understanding of CCSA TAEs regarding the theme in their work environments, as well as to identify the sustainable practices experienced by them in these surroundings. To this end, a qualitative case study of descriptive nature was used, with the use of semi-structured interviews and support of photographic interview with 14 TAEs. As a result, it was observed that the TAES have limited knowledge about the PLS and other instruments related to the theme, what may be an obstacle to its full implementation. In addition, the main sustainable practices identified, such as replacing disposable cups with other durable utensils, and turning off lights and air conditioning, come from individual initiatives of TAEs or are generated by legal imposition, as the case of the implementation of electronic processes. Although they recognize the existence of specific actions aimed at quality of life in the work environment, it was noticed some weakness from the communication instruments used by the institution to disseminate them. Based on the analysis of the UFPB's main normative instruments, it specific budget for sustainable practices. In this sense, it was concluded that, although the theme is contemplated in its institutional policies, there is still no effective policy.